Ovid S. Crohmălniceanu - De la criticul damnat la „Tata Croh“. - Ruxandra Diana, David (Moholea) (Communication Interculturelle et Littérature / Comunicare Interculturală şi Literatură, 2025)
This paper is part of the PhD thesis called 'Ovid S. Crohmălniceanu - A Monography'. Ovid S. Crohmălniceanu is well known for his contribution to Romanian criticism as well as for being a controversial figure due to his devotion to socialist realism. It seems that after the Romanian Revolution in 1989, his profile was not exactly suitable for what is generally considered to be a great critic. Despite his passion for literature and his undisputed cultural taste, despite his vast and rigorous work, his adhesion to Marxism could not be forgiven. While his activity meant more than the excessive praise of the Soviet model in literature, proven by great works such as 'The Romanian Literature Between the Two World Wars', 'The Expressionism in the Romanian Literature' or 'Five Novelists in Five Different Reading Keys', his detractors tried to minimize his important role in the Romanian literature. However, a new generation of young novelists, found guidance and support in a difficult era of censorship and ideological power, and dared go beyond the limits of the official socialist model. Therefore, he became more than a leader of a literary circle: he became a father figure who gained the respect of an entire generation.